The validity of posterior approach in thoracolumbar spine fracture surgery: A study of 104 cases with literature review - Ghassen Elkahla; Amine Trifa; Mehdi Darmoul (Journal of Craniovertebral Junction and Spine)
Background: Thoracolumbar spine fractures are the most common fracture in the whole spine. Their treatment is often surgical and the posterior approach is the most frequently realized. The aim of this study is to evaluate the clinical recovery and the radiological alignment improvement in thoracolumbar spine patient’s trauma operated through posterior approach. Materials and Methods: Retrospective study of 104 thoracolumbar trauma patients operated via posterior approach in our neurosurgery department between 2018 and 2023. Demographic data, clinical, radiological, and surgical characteristics, and outcome were evaluated for each patient. Results: One hundred and four patients were selected; there were 73 males and 31 females with a mean age of 40.94 years. Most of the patients had no significant medical history and were directly transferred from emergency department. Poly trauma was observed in nearly half of the patients. The most common mechanism of injury was fall from height and secondly road traffic accident. At admission, 70% of patients were classified American Spinal Injury Association (ASIA) E, 12.5% ASIA A, and 17.5% had incomplete neurological deficit. Radiological investigations showed that most fractures are located in the thoracolumbar junction (53.85%) followed by lumbar location (36.55%) and thoracic region (9.6%). Most fractures are classified type A (AO classification) with predominance of subtype A3 and A4, frequently located in the thoracolumbar and lumbar region. All patients were operated through posterior approach with pedicle screw fixation and only 36% had in addition posterior decompression. The mean postoperative hospital stay was 5.4 days. The rate of postoperative complications was 2.9%. At the last follow-up, improvement of incomplete neurological deficit was seen in 80% of cases, and a statistically significant correction of the regional kyphosis angle was observed at the thoracolumbar junction. Conclusion: The posterior approach with pedicle screw fixation is an effective technique for the treatment of thoracolumbar fracture, leading to a good clinical recovery and radiological satisfactory alignment in most of cases with low rate of complications.